How do natural disasters affect services trade? - Ankai Xu; Amèvi Rocard Kouwoaye (World Trade Organization (WTO), 2019)
This paper is the first in the literature to examine the impact of natural disasters on trade in services. We measure the magnitude of natural disasters using two distinct sets of variables and quantify the effect of natural disasters on trade in services using a structural gravity model. We find that, overall, natural disasters lead to a decline of services exports of the affected country but have ambiguous effects on its services imports. On average, a large natural disaster can reduce services exports by 2% to 3%. Capital-intensive service sectors such as transport and communications are most affected by a large natural disaster, with the negative impact on communications exports lasting for up to five years after a disaster. We also find consistently across all estimations that the negative impact of natural disasters on services trade is larger than that on merchandise trade.
Keywords: F14; P48; L80; C23; Q54; H84; 330; international trade; gravity model; services; natural disasters; climate change